Answers

2014-11-04T09:48:42+08:00
I think your question lack details... please give more details... thanks

-----

I dunno how to add another answer so I'll just edited this one

your given is m = 1 (2,5)

the formula is y - ysub1 = m (x - xsub1)

here (xsub1, ysub1) = (2,5)

meaning

xsub1 = 2 and ysub1 = 5

therefore,

y - 5 = 1(x - 2)

multiply first the 1 to x -2

we have

y - 5 = x - 2

then move 5 to the other side and change it's sign

we have

y = x - 2 + 5

then add -2 to 5

we have

y = x + 3

---

so you have y = x + 3 as your equation

I hope it helps.


0
thank you very much
questions again about the same asked questions. (-7,4) and (5-2) =-2/6
write the equation of the ff. line that passing through the given
write the equation of the ff. line that passing through the given (-7.4) and (5-2) =-2/6
you just need to replace the xsub1 and ysub1 kid